Development of web-based Small-Scale Irrigation Management Information System (SSIMIS) to facilitate data collection, storage, management, and analysis - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The SSMIS prototype dashboard is under development by employing a combination of three integrated approaches: advanced geospatial analysis and remote sensing, citizen science, and machine learning approaches. The system will be able to provide timely, accurate and a readily available database on small-scale irrigation schemes, to be ready by 2021.